Molecular Phylogeny and Evolution of Morphology in the Social Amoebas - Pauline Schaap; Thomas Winckler; Michaela Nelson; Elisa Alvarez‐Curto; Barrie Elgie; Hiromitsu Hagiwara; James C. Cavender; Alicia Milano-Curto; Daniel E. Rozen; Theo Dingermann; Rupert Mutzel; Sandra L. Baldauf (2006)
The social amoebas (Dictyostelia) display conditional multicellularity in a wide variety of forms. Despite widespread interest in Dictyostelium discoideum as a model system, almost no molecular data exist from the rest of the group. We constructed the first molecular phylogeny of the Dictyostelia with parallel small subunit ribosomal RNA and a-tubulin data sets, and we found that dictyostelid taxonomy requires complete revision. A mapping of characters onto the phylogeny shows that the dominant trend in dictyostelid evolution is increased size and cell type specialization of fruiting structures, with some complex morphologies evolving several times independently. Thus, the latter may be controlled by only a few genes, making their underlying mechanisms relatively easy to unravel.